Juridical Analysis of the Draft Law on Protection and Legal Certainty (RUU PPRT) for Female Domestic Helpers in Medan City - Panjaitan, Rizal; Lubis, Syofiaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The legal protection of domestic helpers is one at the implementation level that should be protected by the state considering that the constitution itself has guaranteed certainty, equality, and legal protection to all Indonesian citizens without excluding them. The state, as a facilitator in the private sphere, should be responsible for protecting women domestic workers by formulating comprehensive regulations along with the institutions that organize them so as to shape the sociocultural society towards a domestic worker-friendly direction. Unfortunately, the existing laws do not accommodate legal protection for female domestic workers. Their only hope now is in the Ministerial regulation, but at that level, there are still polemics such as overlapping. Based on these problems, it is necessary to reconstruct the law that answers in substance, structure, and culture. The research method used qualitatively is the PPRT Bill Approach. his research concludes that the absence of adequate legal protection for female domestic workers is due to the absence of legal recognition that can provide certainty and legal protection for them. Therefore, it is necessary to initiate legal protection for domestic workers on the basis of the Draft Law on the Protection and Legal Certainty of Female Domestic Helpers in Indonesia and especially in Medan.